1998
DOI: 10.1093/ndt/13.8.2037
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac valve calcification in haemodialysis patients: role of calcium-phosphate metabolism

Abstract: Our study confirmed an increased prevalence of VC in HD patients and selected age and calcium phosphate product as the most predictive parameters. These findings support careful monitoring of calcium metabolism beginning at the early stages of end-stage renal failure to reduce the risk of heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
197
7
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(225 citation statements)
references
References 7 publications
10
197
7
11
Order By: Relevance
“…Inflammatory molecules, modified lipids, infectious agents, and circulating levels of calcium and phosphate have been proposed as potential promoters of valve calcification. 1,6,7 However, little is known about the effects of these factors on the calcifying behavior of aortic valve interstitial cell (VIC) subpopulations. We and others have previously shown in the porcine and human system that VIC represent a phenotypically heterogeneous population of cells mainly composed by fibroblasts/myofibroblasts/smooth muscle (SM) cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory molecules, modified lipids, infectious agents, and circulating levels of calcium and phosphate have been proposed as potential promoters of valve calcification. 1,6,7 However, little is known about the effects of these factors on the calcifying behavior of aortic valve interstitial cell (VIC) subpopulations. We and others have previously shown in the porcine and human system that VIC represent a phenotypically heterogeneous population of cells mainly composed by fibroblasts/myofibroblasts/smooth muscle (SM) cells.…”
mentioning
confidence: 99%
“…7 Increased level of serum phosphate which typically occurs in these patients is now considered relevant for the progression of vascular calcification. Seminal work by Giachelli's group demonstrated that phosphate could induce a phenotypic switch of SM cells toward an osteoblast/chondrocyte profile and promote calcium deposition in vitro.…”
mentioning
confidence: 99%
“…The administration of such compounds, however, contributes to the development of frequent episodes of hypercalcemia, hyperphosphatemia, adynamic osteodystrophy, and vascular calcifications (2)(3)(4)(5)(6)(7)(8). Indeed, current evidence indicates that abnormalities in mineral metabolism, as well as the therapeutic agents that are most widely used for the treatment of 2°HPT, play a role in the development of vascular calcifications in adult and pediatric patients with ESRD (2,4,5) and may contribute to decreased overall survival in ESRD (9 -11).…”
mentioning
confidence: 99%
“…[1,2] Excess phosphorus combines with calcium and deposits in arteries and other soft tissues and leads to the development of atherosclerotic heart disease. [3] Elevated serum phosphorus also stimulates parathyroid hormone and contributes to secondary hyperparathyroidism and renal bone disease. [1,4,5] The amount of phosphorus in the American diet has increased considerably, primarily from phosphorus containing additives in convenience and fast foods.…”
Section: Introductionmentioning
confidence: 99%